2021
DOI: 10.1093/cvr/cvab237
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-5-induced eosinophil population improves cardiac function after myocardial infarction

Abstract: Aims Interleukin (IL)-5 mediates the development of eosinophils (EOS) that are essential for tissue post-injury repair. It remains unknown whether IL-5 plays a role in heart repair after myocardial infarction (MI). This study aims to test whether IL-5-induced EOS population promotes the healing and repair process post-MI and to reveal the underlying mechanisms. Method and results MI was induced by permanent ligation of the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 59 publications
0
33
2
Order By: Relevance
“…Recently, it has been shown that eosinophil recruitment to the heart is beneficial during myocardial infarction (55)(56)(57). This seems at first contradictory to our findings presented here but it is likely that different mechanisms are at play.…”
Section: Discussioncontrasting
confidence: 99%
“…Recently, it has been shown that eosinophil recruitment to the heart is beneficial during myocardial infarction (55)(56)(57). This seems at first contradictory to our findings presented here but it is likely that different mechanisms are at play.…”
Section: Discussioncontrasting
confidence: 99%
“…IL-5 has been widely investigated in allergic diseases as a member of the β common chain cytokine family [ 11 , 45 , 46 ]. Recent research suggests that IL-5 improves cardiac function after AMI by modulating local inflammatory conditions [ 16 ]. This therapeutic effect is mainly achieved by increasing the EOS population in the infarcted myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Following surgery, all mice were randomized into three groups: PBS (300 μl), NP IL-5 (300 μl), and NM-NP IL-5 (300 μl) (intravenous injection). The total dosage of IL-5 was administrated at 100ug/kg, as described in detail by Xu et al [ 16 ]. Mice were sacrificed on days 3 and 7 for short-term experiments and day 28 for long-term experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the ILC2-related cytokine IL-5, Xu et al. ( 57 ) reported that it facilitates recovery of cardiac function post-MI by promoting eosinophil accumulation and subsequent CD206 + macrophage polarization via the IL-4/STAT6 axis. The ILC2-related cytokine IL-13 could regulate leukocyte recruitment and induce differentiation of M2-like monocytes/macrophages, and could promote recovery of cardiac function after MI by secreting anti-inflammatory cytokines to stimulate new blood vessel formation and collagen deposition, thereby enhancing wound healing in the infarct area ( 26 ).…”
Section: The Role Of Ilcs In Repair and Regeneration After MImentioning
confidence: 99%